Bimetallic Pt–Sn/γ-Al2O3 catalyzed β-alkylation of secondary alcohols with primary alcohols under solvent-free conditions. Issue 36 (7th September 2016) - Wu, Kaikai; He, Wei; Sun, Chenglin; Yu, Zhengkun
Graphical abstract: Highlights: Pt–Sn/γ-Al2 O3 catalyzed β-alkylation of secondary alcohols with primary alcohols. The reaction underwent through a hydrogen borrowing strategy. Atom-economical and environmentally benign C–C bond formation is presented. Abstract: Heterogeneous bimetallic Pt–Sn/γ-Al2 O3 (0.5 wt% Pt, molar ratio Pt:Sn = 1:3) was successfully utilized as the catalyst for direct β-alkylation of secondary alcohols with primary alcohols under solvent-free conditions. β-Alkylated secondary alcohols were obtained in moderate to high yields with water formed as the by-product through a hydrogen borrowing pathway. The present protocol provides a concise atom-economical and environmentally benign method for C–C bond formation.